Walking ability of broilers with different gait scores - Almeida Paz, I. C.L. [UNESP] (2015)
The study was conducted at the School of Veterinary Medicine of Animal Science, Brazil (22°53′16″S and 48°26′45″W). The experimental design was completely randomized with a 2x2 factorial treatment (two strains - Cobb®500 and Ross®308 and two sexes), with six replicates of 50 birds each. The aim was to evaluate the walking ability of broilers with different gait scores. The study used 1,200 one-day-old broilers, all receiving a diet with the same nutritional composition. At 40 days, the gait score (GS) of all the birds was assessed and birds were assigned grades between 0 (optimal GS) and 5 (bird could not walk). The walking ability of six birds with each score in each treatment was then filmed for assessment purposes. These broilers were medicated orally with an analgesic solution of metanizole sodium and filmed again after 60 minutes. Software was used to take three measurements of average speed achieved by representative broilers with each GS. The data were analysed using software from SAS. Analysis of variance (ANOVA) was performed and means were compared using the Tukey test at 5% probability. There was no difference between strains (p>0.05). There was a difference (p<0.05) in average speed between GS 0 and the other GS levels without the use of analgesics. However, when the birds were medicated there was an increase in bird speed (p < 0.05), especially in GS 2, 3 and 4. The males were slower than the females because males were heavier and showed less walking ability The time taken to walk one metre decreases when the birds are medicated with analgesics.